Chemokines and their receptors: their biology and therapeutic relevance - Proudfoot, Amanda (Henry Stewart Talks, 2012)
Chemokines are immune modulators regulating direction of cell migration, Chemokine receptors are seven transmembrane (7TM) G protein-coupled receptors, Chemokines need to bind to endothelial expressed proteoglycans for activity in vivo, Excessive cell recruitment is a hallmark of inflammation, 7TM receptors are highly druggable targets for the pharmaceutical industry, Chemokine receptors are an essential co-receptor for HIV infectivity, Nature uses chemokine binding proteins to iinhibit the chemokine system